PEMANFAATANINTERNETSEHATSEBAGAISUMBER BELAJAR PADA PROGRAM PENDIDIKAN KESETARAAN DI SANGGAR KEGIATAN BELAJAR KOTA SEMARANG - Ardianto, Noor Indra (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
"Community nowadays, demand a higher quality of education in Indonesia, it is a challenge for non-formal education executant. Utilization of the Internet as a learning resource on equivalency education program in the Sanggar Kegiatan Belajar (SKB), is one of the changes made in the counterbalance to date. A Safe and Healthy use of the Internet as a learning resource is expected to assist in improving the quality of learning in the SKB, in order to create graduates who can compete (at least close to) with the graduates of formal schooling. "